Moisture dependent engineering properties of onion (Allium cepa var aggregatum) umbels - PRAGALYAASHREE, M M; KAILAPPAN, R (The Indian Journal of Agricultural Sciences, 2014)
Physical properties of onion (Allium cepa var aggregatum L.) umbels namely size, shape, bulk density, particle density, angle of repose, frictional properties etc., were determined as a function of moisture content in the moisture range of 10.26 to 50.15% (db). These important physical properties of onion umbels are necessary for the design and development of machines for threshing, cleaning and handling operations of onion umbels. The average length, width and thickness of onion umbels varied from 49.66 to 50.24, 47.20 to 50.20 and 34.89 to 37.69 mm respectively. Average geometric mean diameter of the umbels varied from 43.01 to 46.03 mm while sphericity and mass of hundred umbels (M100) increased from 0.855 to 0.885 and 267.36 to 487.42 g as the moisture content increased in the above range. Bulk density and true density of onion umbels increased from 61.26 to 156.12 and 141.05 to 297.02 kg/m3 respectively for the above said increase in moisture content. Porosity and angle of repose of umbel increased linearly from 45.95 to 56.55% and 30.83 to 38.13° respectively with increase in moisture content from 10.26 to 50.15%. The coefficient of friction of onion umbels also increased linearly with increase in moisture content of umbels on different surfaces. From the investigation on the physical properties of onion umbels, viz. bulk density, true density, porosity, angle of repose, static coefficient of friction on various surfaces, viz. mild steel, rubber sheet, galvanised-iron sheets, aluminium sheets, cardboard sheets and stainless steel sheets increased linearly with increase in the moisture range between 10.26 to 50.15% (db).